What is the average rate of change of `f(x)=-x^3+1` from 1 to 3?

1 Answer | Add Yours

justaguide's profile pic

justaguide | College Teacher | (Level 2) Distinguished Educator

Posted on

The average rate of change of f(x) = `-x^3 + 1` from 1 to 3 has to be determined.

This is given by `(f(3) - f(1))/(3 - 1)` = `((-3)^3 + 1 - (-1)^3 - 1)/2` = `(-27 + 1)/2` = -13

The average rate of change of `f(x) = -x^3 + 1` from 1 to 3 is -13

We’ve answered 318,983 questions. We can answer yours, too.

Ask a question